Leaf morphological strategies of seedlings and saplings of Rhizophora mangle (Rhizophoraceae), Laguncularia racemosa (Combretaceae) and Avicennia schaueriana (Acanthaceae) from Southern Brazil - Pelozo, Andressa (2016)
The initial phase of a plant life cycle is a short and critical period, when individuals are more vulnerable to environmental factors. The morphological and anatomical study of seedlings and saplings leaf type, enables the understanding of species strategies of fundamental importance in their establishment and survival. The objective of this study was to analyze the structure of seedlings and saplings leaf types of three mangrove species, Avicennia schaueriana, Laguncularia racemosa, Rhizophora mangle, to understand their early life adaptive strategies to the environment. A total of 30 fully expanded cotyledons (A. schaueriana and L. racemosa), 30 leaves of seedlings, and 30 leaves of saplings of each species were collected from a mangrove area in Guaratuba Bay, Paraná State, Brazil. Following standard methods, samples were prepared for morphological (leaf dry mass, density, thickness) and anatomical analysis (epidermis and sub-epidermal layers, stomata types, density of salt secretion glands, palisade and spongy parenchyma thickness). To compare leaf types among species one-way ANOVA and Principal Component Analysis were used, while Cluster Analysis evaluated differences between the species. We observed significant structural differences among species leaf types. A. schaueriana showed the thickest cotyledons, while L. racemosa presented a dorsiventral structure. Higher values of the specific leaf area were observed for seedlings leaves of A. schaueriana, cotyledons of L. racemosa and saplings leaves of A. schaueriana and R. mangle. Leaf density was similar to cotyledons and seedlings leaves in A. schaueriana and L. racemosa, while R. mangle had seedlings leaves denser than saplings. A. schaueriana and R. mangle showed hypostomatic leaves, while L. racemosa amphistomatic; besides, A. chaueriana showed diacytic stomata, while L. racemosa anomocytic, and R. mangle ciclocytic. Seedling leaves were thicker in R. mangle (535 µm) and L. racemosa (520 µm) than in A. schaueriana (470.3 µm); while saplings leaves were thicker in L. racemosa (568.3 µm) than in A. schaueriana seedlings (512.4 µm) and R. mangle (514.6 µm). Besides, seedlings leaves palisade parenchyma showed increasing thickness in L. racemosa (119.2 µm) < A. schaueriana (155.5 µm) < R. mangle (175.4 µm); while in saplings leaves as follows R. mangle (128.4 µm) < A. schaueriana (183.4 µm) < L. racemosa (193.9 µm). Similarly, seedlings leaves spongy parenchyma thickness values were as follows A. schaueriana (182.6 µm) = R. mangle (192.8 µm) < L. racemosa (354.4 µm); while in saplings were A. schaueriana (182.6 µm) = R. mangle (187.3 µm) < L. racemosa (331.3 µm). The analyzed traits, in different combinations, represent morphological adjustments of leaf types to reduce water loss, eliminate salt excess, increase the absorption of light, allowing a higher efficiency on the maintenance of physiological processes in this initial growth stage.